2001
DOI: 10.1111/j.1365-2621.2001.tb04594.x
|View full text |Cite
|
Sign up to set email alerts
|

Milk Protein Coatings Prevent Oxidative Browning of Apples and Potatoes

Abstract: Color analysis on apple and potato slices coated with calcium caseinate or whey protein solutions showed that the 2 coatings efficiently delayed browning by acting as oxygen barriers. The antioxidant properties of the films were realized using a model allowing the release of oxidative species by electrolysis of saline buffer. Whey proteins were a better antioxidant capacity than calcium caseinate. Furthermore, addition of carboxymethyl cellulose (CMC) to the formulations significantly improved their antioxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(77 citation statements)
references
References 19 publications
4
68
0
5
Order By: Relevance
“…The WPI forms a reference to better understand the antioxidant properties of chickpea proteins due to its well known antioxidant potential (Hu et al, 2003;Le Tien et al, 2001;Tong et al, 2000). As expected, the free radical scavenging capacity of lyophilized HCPE is almost 1.9-fold higher than that of CPE.…”
Section: Effect Of Pepsin Hydrolysis On Antioxidant Potentialsupporting
confidence: 53%
See 1 more Smart Citation
“…The WPI forms a reference to better understand the antioxidant properties of chickpea proteins due to its well known antioxidant potential (Hu et al, 2003;Le Tien et al, 2001;Tong et al, 2000). As expected, the free radical scavenging capacity of lyophilized HCPE is almost 1.9-fold higher than that of CPE.…”
Section: Effect Of Pepsin Hydrolysis On Antioxidant Potentialsupporting
confidence: 53%
“…The functional properties including antioxidant activity have been studied most extensively for soybean and milk proteins (Chove, Grandison, & Lewis, 2007;Hu et al, 2003;Le Tien, Vachon, Mateescu, & Lacroix, 2001;Tong, Sasaki, McClements, & Decker, 2000;Webb, Naeem, & Schmidt, 2002). Different studies have also been conducted to improve functional properties of these proteins by enzymatic hydrolysis (Chen, Muramoto, & Yamauchi, 1995;Pacheco, Amaya-Farfan, & Sgarbieri, 2002;Penas, Prestamo, & Gomez, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…These coatings have gained immense recognition in being environment friendly, biodegradable, non-toxic and rather safe choice to be used in food applications (Sánchez-González et al, 2011). Starch, alginate and Chitosan are among the polysaccharide based edible coatings with their usage assessed in different coating formulations (Tien et al, 2001). Considering the above mentioned facts the present study has been planned to address the socio-economic indicators of developing countries like Pakistan where large quantity of fresh horticulture produce goes waste as a victim to inadequate and improper handling and storage conditions.…”
Section: Introductionmentioning
confidence: 99%
“…More than twenty years ago Nisperos-Carriedo et al [19] demonstrated that edible coatings based on cellulose gums effectively delay ripening in some climacteric fruits like mangoes, papayas, and bananas and significantly reduce enzymatic browning on sliced mushrooms. Ten years later Le Tien et al [20] showed that milk protein coatings are able to counteract oxidative degradation of cut fruits and vegetables through polyphenol oxidase inhibition. From then several polysaccharides (chitosan, alginate, methylcellulose or pectin) and proteins (casein, collagen, gelatin, phaseolin, zein, soy or whey proteins), or mixtures of them, were shown to give rise to edible films effective as water vapor and gas barriers for a wide range of food products and as carriers for antimicrobials [17,[21][22][23][24][25].…”
mentioning
confidence: 99%